Potential water resource impacts of hydraulic fracturing from unconventional oil production in the Bakken shale. (1st January 2017) - Shrestha, Namita; Chilkoor, Govinda; Wilder, Joseph; Gadhamshetty, Venkataramana; Stone, James J.
Abstract: Modern drilling techniques, notably horizontal drilling and hydraulic fracturing, have enabled unconventional oil production (UOP) from the previously inaccessible Bakken Shale Formation located throughout Montana, North Dakota (ND) and the Canadian province of Saskatchewan. The majority of UOP from the Bakken shale occurs in ND, strengthening its oil industry and businesses, job market, and its gross domestic product. However, similar to UOP from other low-permeability shales, UOP from the Bakken shale can result in environmental and human health effects. For example, UOP from the ND Bakken shale generates a voluminous amount of saline wastewater including produced and flowback water that are characterized by unusual levels of total dissolved solids (350 g/L) and elevated levels of toxic and radioactive substances. Currently, 95% of the saline wastewater is piped or trucked onsite prior to disposal into Class II injection wells. Oil and gas wastewater (OGW) spills that occur during transport to injection sites can potentially result in drinking water resource contamination. This study presents a critical review of potential water resource impacts due to deterministic (freshwater withdrawals and produced water management) and probabilistic events (spills due to leaking pipelines and truck accidents) related to UOP from the Bakken shale in ND. Graphical abstract: Highlights: Summary of Bakken shale members and Williston basin. Water footprint and water contamination due to hydraulic fracturing in ND. Unconventional oil production, water use and brine spills in ND. Geochemical and strontium isotope tracers for brine spill detection in ND. Transportation hazards and corrosion problems in ND.